Reform Perspectives on Welfare State Models in Global Capitalism - Karl Aiginger; Alois Guger; Thomas Leoni; Ewald Walterskirchen (Austrian Institute of Economic Research (WIFO), 2007)
The paper characterises a number of welfare state models in the tradition of Esping-Andersen, analysing the economic and social performance of these different welfare regimes on an encompassing empirical basis both in the long run and with respect to their adaptability to the challenges of the last decades. While the differences with regard to growth dynamics had been very small in the decades after World War II (1960-1990), growth rates as well as the employment and social policy records have diverged over the past 15 years. The best performances were found for the extremes: the Scandinavian model and the liberal Anglo-Saxon model, while the continental model produced low growth and increasing unemployment. The reforms primarily in the Scandinavian countries allow us to delineate elements of a "New Welfare State Architecture" which on the one hand upholds important characteristics of a European social model, but on the other hand allows welfare states to be competitive in the globalising economy. Such a European socio-economic model could redirect incentives in such a way that the welfare state is able to shift from a burden (increasing costs and lowering flexibility) to a productive force.
Keywords: 330; welfare state; social model; economic performance; reform policies; Sozialstaat; Wirtschaftswachstum; Soziale Lage; Europa